Managing the documents in Old Mongol writing at the National Archives of the Republic of Tuva: history and issues of improvement - Samdan, Ayana A. (The New Research of Tuva, 2020)
The article traces the history of managing the massive of documents in Old Mongolian writing preserved at the National Archives (prior to 07.04.2020 known as the State Archives) of the Republic of Tuva. We focus on Mongol fond No. 115, since all other fonds which contain Mongolian documents later split away from this collection. The fond covers documents created over a large span of time: the Qing period (early 18th century to 1912), the short period of the Russian protectorate (1914-1921) and the first decade of the Tuvan People’s Republic (1921-1933). All of the documents are in Old Mongolian language.The history of the fond is part and parcel of the history of the archive itself. Originally, the documents were grouped together by their chronological, thematic and subject matter features. Traditional chronological record keeping was accompanied by having some of the documents translated into Tuvan. In the Soviet years, archival work followed the common USSR guidelines. While the amount of archival material grew, there was an obvious lack of well-trained specialists who both knew Tuvan history and could read Old Mongolian writing. Documents have been moved between fonds. A significant contribution to studying the Mongolian fond was made by Buryat scholar P.B. Baldanzhapov (born 1957).Materials preserved in the fond were actively studied and used in 2011-2014 when the Archives did a joint project with Tuvan Institute for the Humanities and Applied Socioeconomic Studies. 4 volumes of “A collection of archival documents on the history of Tuva” were published between 2011 and 2014.At the moment, Fond 115 is still being improved, with an electronic catalogue to be set up. Other plans include digitizing and restoring the documents.
Keywords: Tuva; archive; State Archives of the Republic if Tuva; National Archives of the Republic of Tuva; Old Mongolian writing; Mongolian language; archival document; digitization